Probiotic supplementation attenuated early-life chemotherapy-induced brain development impairment in mice - Tan, Aihua; Chen, Jie; Zhang, Juan; Tong, Jianbin; Jiang, Zhibin (Frontiers in Behavioral Neuroscience, 2025)
BackgroundBrain dysfunction is a common post-chemotherapy sequela in acute lymphoblastic leukemia (ALL) survivors and is associated with poor academic performance and reduced work ability. The prevention of brain dysfunction in ALL survivors remains a clinical challenge. In this study, we evaluated the preventive effects of probiotics on chemotherapy-induced brain development damage in a preclinical setting.MethodsThe clinical ALL chemotherapy setting was mimicked by intraperitoneally injecting doxorubicin into 4-week-old mice once every 3 days for 2 weeks. Probiotics were administered in the drinking water from the beginning of chemotherapy until adulthood. Behaviors at adulthood were assessed using open field, elevated plus maze, novel object recognition, and Barnes maze tests. Fecal microbiota composition was analyzed using 16S ribosomal RNA (rRNA) gene sequence. Hippocampal neurogenesis was assessed using EdU staining and DCX immunostaining. Synaptic protein expressions were detected using Western blotting.ResultsEarly-life chemotherapy induced cognitive dysfunction in adulthood, as demonstrated by impairments in the novel object recognition and Barnes maze tests, but it did not significantly alter anxiety-like behavior in the elevated plus maze. Early-life chemotherapy also induced fecal microbiota dysbiosis both at the end of chemotherapy and in adulthood. Probiotic supplementation alleviated early-life chemotherapy-induced cognitive dysfunction and fecal microbiota dysbiosis in adulthood. In addition, probiotic supplementation also alleviated early-life chemotherapy-induced hippocampal neurogenesis impairments and synaptic protein loss.ConclusionProbiotic supplementation can improve early-life chemotherapy-induced brain development impairments in mice by modulating hippocampal neurogenesis.